2007
DOI: 10.1007/s11199-007-9258-5
|View full text |Cite
|
Sign up to set email alerts
|

The Femininity Ideology Scale: Factor Structure, Reliability, Convergent and Discriminant Validity, and Social Contextual Variation

Abstract: This study reports on the psychometric properties of the Femininity Ideology Scale (FIS) from the responses of 407 undergraduate participants in the USA. Factor analysis supported the five factor structure. Cronbach alpha coefficients of the factors and total scale were adequate. Support for discriminant validity was found after examining the relationship between the FIS and the Bem Sex Role Inventory, which measures feminine traits. Support for convergent validity was found after examining, first, with the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 27 publications
4
94
0
4
Order By: Relevance
“…First, culturally popular efforts to maintain or reclaim masculinity, from the founding of the Boy Scouts of America to the mythopoetic movement (e.g., Bly 1990;Hantover 1978), have repeatedly equated "traditional" masculinity with activities in nature and have positioned "civilization" as un-masculine (Connell 1995;Kilmartin 2007), while changes in women's roles and femininity have often been attributed to cultural changes (Hochschild andMachung 1989/2003;Stewart and Ostrove 1998). Second, males report greater support for traditional gender roles and stereotype gender more strongly (Levant et al 2007;Strough et al 2007;Twenge, 1997a;Vogel et al 2003), which suggests less flexibility and may be the result of the positioning of masculinity as natural. Similarly, males are taught to avoid femininity (Connell 1995;O'Neil et al 1986), receive less encouragement for and are less likely to adopt feminine behaviors and traits (Sirin et al 2004;Smiler et al 2008;Twenge 1997b), and are more strongly punished for demonstrating cross-gender behavior (Bartlett et al 2002;Carver et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…First, culturally popular efforts to maintain or reclaim masculinity, from the founding of the Boy Scouts of America to the mythopoetic movement (e.g., Bly 1990;Hantover 1978), have repeatedly equated "traditional" masculinity with activities in nature and have positioned "civilization" as un-masculine (Connell 1995;Kilmartin 2007), while changes in women's roles and femininity have often been attributed to cultural changes (Hochschild andMachung 1989/2003;Stewart and Ostrove 1998). Second, males report greater support for traditional gender roles and stereotype gender more strongly (Levant et al 2007;Strough et al 2007;Twenge, 1997a;Vogel et al 2003), which suggests less flexibility and may be the result of the positioning of masculinity as natural. Similarly, males are taught to avoid femininity (Connell 1995;O'Neil et al 1986), receive less encouragement for and are less likely to adopt feminine behaviors and traits (Sirin et al 2004;Smiler et al 2008;Twenge 1997b), and are more strongly punished for demonstrating cross-gender behavior (Bartlett et al 2002;Carver et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it seems that men may adhere more rigorously to social norms than do women, for fear of the negative consequences of diverging from traditional roles (Schrock & Schwalbe, 2009). That is, men (both heterosexual and homosexual) face greater social restrictions against stereotypically feminine behaviour (David & Brannon, 1976;Levant et al, 2007;Taywaditep, 2001). In contrast, the rise of the feminist movement encouraged "masculine empowerment" in women (Connell, 1993;Lisak, 2000, as cited by Smiler, 2004) and removed many of the former restrictions on acceptable behaviour for women.…”
Section: Initial Resultsmentioning
confidence: 99%
“…According to Levant et al (2007), consequences of this phenomenon, known as Gender Role Strain (Pleck, 1995), include low self-esteem, difficulty in intimate relationships, high anxiety, alexithymia, and depression. Research has demonstrated negative psychological and social consequences of stereotypical ideologies (Schrock & Schwalbe, 2009), leading to believe that the popularization of a more flexible conceptualization of sex roles could be beneficial for young men.…”
Section: Resultsmentioning
confidence: 99%
“…Vakarietiškose kultūrose vyrauja įsitikinimas, kad moteriška mergina turi būti maloni, besirūpinanti kitų jausmais, emocionali, jautri, paklusni, o kalbant apie išvaizdą -liekna, grakšti ir daili (Blakemore, Berenbaum, Liben, 2009;Levant, Richmond, Cook, House, Aupont, 2007;Mahalik, Morray, Coonerty-Femiano, Ludlow, Slattery, Smiler, 2005). Nors dažniausiai apibūdina-mas panašiai, vis dėlto moteriškumo sąvokos turinys nėra ksuotas, kinta pagal kultūrinį kontekstą ir pasirinktą teorinę perspektyvą.…”
Section: Moteriškumo Samprata Ir Jos Pokyčiai Psichologiniuose Tyrimuoseunclassified
“…Nors dažniausiai apibūdina-mas panašiai, vis dėlto moteriškumo sąvokos turinys nėra ksuotas, kinta pagal kultūrinį kontekstą ir pasirinktą teorinę perspektyvą. Skirtingais laikotarpiais ir iš skirtingų perspektyvų psichologijos mokslinėje literatūro-je moteriškumas buvo suprantamas ir kaip tam tikri bruožai (Bem, 1981;Bem, Martyna, Watson, 1976), ir kaip nuostatos (Galambos, Petersen, Richards, Gitelson, 1985) ar ideologijos (Tolman, Porche, 2000;Levant, Richmond, Cook, House, Aupont, 2007), ir kaip daugiamatis konstruktas, apimantis tiek bruožus, tiek nuostatas, tiek elgesį (Spence, 1993;Liben, Bigler, 2002). Moterų psichikos sveikatos tyrimų kontekste svarbiausia išsiaiškinti moteriškumo, kaip ekspresinių bruožų, ir moteriškumo ideologijos sampratų skirtumus bei sąsajas.…”
Section: Moteriškumo Samprata Ir Jos Pokyčiai Psichologiniuose Tyrimuoseunclassified